Oil-Adjuvanted Polyvalent Formalin-Killed Aeromonas hydrophila Vaccine Enhances Agglutinating Antibodies, Respiratory Burst, and Survival in Giant Gourami - Rozi; Tyasningsih, Wiwiek; Rahmahani, Jola; Aksono, Eduardus Bimo; Yunus, Muchammad; Arif, Mohammad Anam Al; Kuncorojakti, Suryo; Nindarwi, Daruti Dinda; Sari, Putri Desi Wulan; Dewi, Nina Nurmalia; Satyantini, Woro Hastuti; Santanumurti, Muhammad Browijoyo; et al. (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Motile Aeromonas septicaemia (MAS), predominantly associated with Aeromonas hydrophila, remains a major constraint in giant gourami (Osphronemus goramy) aquaculture. This study evaluated formalin-inactivated A. hydrophila vaccines prepared from MAS-associated field isolates, comparing a monovalent formulation (P2), a non-adjuvanted polyvalent formulation (P3), and an oil-adjuvanted polyvalent formulation (P4) against PBS controls (P1). A total of 240 fish were used (60 per treatment) and assigned to two parallel cohorts (immunology and survival/challenge). Immune endpoints (agglutinating titres, NBT activity, and splenic il-1β and ifn-γ transcription) were assessed on days 7, 14, 21, 35, and 42 post-vaccination. The survival cohort was challenged intraperitoneally at day 21 with a homologous A. hydrophila strain and monitored for 14 days post-challenge. Vaccination was clinically well tolerated and improved survival relative to controls, with P4 showing the highest protection (RPS 81.8%). Agglutinating titres differed by treatment and time; at the peak sampling point (day 35), mean titres in P4 were ~200-fold higher than in P1, and model contrasts indicated significant differences versus controls (p<0.001). Splenic il-1β and ifn-γ transcript levels were higher in vaccinated groups than in controls at later time points. These findings support further evaluation of an oil-adjuvanted polyvalent inactivated A. hydrophila vaccine for gourami, including dose optimisation, extended safety assessment, heterologous challenge, and field validation.